Fluidization of palm kernel shell, palm oil fronds, and empty fruit bunches in a swirling fluidized bed gasifier. (4th March 2017) - Shahbaz, M.; Yusup, S.; Naz, M. Y.; Sulaiman, S. A.; Inayat, A.; Partama, A.
ABSTRACT: The increased biomass utilization has triggered the use of palm oil waste as fuel for gasification in Malaysia. In this study, pioneering work was conducted on three types of palm oil wastes namely palm kernel shell (PKS), palm oil fronds (POF), and empty fruit bunches (EFB). Minimum air velocity ( U mf ) required for fluidization of the tested biomass was determined experimentally in a swirling fluidized bed, by considering the effect of bed weight, density, particle size, fluidized bed height, pressure drop, and bed voidage. It was revealed that higher the particle size the smaller will be the voidage, which consequently affects the minimum fluidization velocity. U mf was increased with a decrease in voidage size. However, a direct relationship was found between particle size and U mf . Overall highest U mf was determined for EFB followed by POF and PKS. Fluidized bed height was increased by decreasing the particle size regardless of the biomass type. Highest unsettled bed height was obtained with PKS on account of its low density among all the test fuels. It was concluded that optimization of the fluidized bed for each type of biomass, particle size, and density is explicitly required for a low-cost energy conversion process.